If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 4(-5 + 3G) = 1 + -1g 5y + (-5 * 4 + 3G * 4) = 1 + -1g 5y + (-20 + 12G) = 1 + -1g Reorder the terms: -20 + 12G + 5y = 1 + -1g Solving -20 + 12G + 5y = 1 + -1g Solving for variable 'G'. Move all terms containing G to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 12G + 20 + 5y = 1 + 20 + -1g Reorder the terms: -20 + 20 + 12G + 5y = 1 + 20 + -1g Combine like terms: -20 + 20 = 0 0 + 12G + 5y = 1 + 20 + -1g 12G + 5y = 1 + 20 + -1g Combine like terms: 1 + 20 = 21 12G + 5y = 21 + -1g Add '-5y' to each side of the equation. 12G + 5y + -5y = 21 + -1g + -5y Combine like terms: 5y + -5y = 0 12G + 0 = 21 + -1g + -5y 12G = 21 + -1g + -5y Divide each side by '12'. G = 1.75 + -0.08333333333g + -0.4166666667y Simplifying G = 1.75 + -0.08333333333g + -0.4166666667y
| mn+7p=8 | | 3x-2x+4=2+x+2 | | 2.5(2x+5)=5(x+2.5) | | -3(n-4)-27=17 | | v-5=7+5(8-5v) | | 6(-4+2x)=-132 | | 11-8x=3(1-3x) | | m^2-20=0 | | 12x^2-38x-12=0 | | 4g-3g=1+g | | -18-4n=-7(2n-6) | | -8x-40=4(-4x-6) | | 16x^6y^10=0 | | 10+15y=75y-2 | | -7(3b-7)=-2b+30 | | 8x^2-2x+4=0 | | [5x-2]=12 | | 8x-6+10x-12=180 | | 8x^2-2x+4=y | | 2m^2-13m+6=0 | | 4(x-4)=5-3x | | x+17=3x-35 | | 11=17-2b | | -33+6b=-(b-2) | | x+9=3x-37 | | 8034*n=80.34 | | 0.5d-0.83d=4 | | 8(7x-1)=64 | | 3x-9=6x+36 | | 4x=(23x+18) | | 12x^2-200=0 | | 14-2x=-5x |